Factor analysis: An instrument for selection of social performance factors - Jana Hornungová (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2014)
This article is focused on the identification of social performance factors. For this purpose, a multidimensional statistical method -factor analysis was used. The basic set for the selection of indicators was the concept (and the social tool) of Corporate Social Responsibility, subsequently, the question- naire was constructed. Empirical research was attended by 32 companies, from the Area of Information and Communication Activities (CZ-NACE, section J), with the number of employees over 250. The aim of the factor analysis was selection of significant indicators and performance factors for selected area from the input database. On the basis of the paper, there were evaluated: three social factors from the area of working environment and two social factors from the area of local commu- nity. The understanding of their application into the internal management shall be necessary prior to company's decision regarding the measures of key performance indicators.
Keywords: M21; M14; C42; 330; business management; performance; indicators; factor analysis